Better than any pill - and no side effects! Healthy lifestyles, statins and aspirin - Elwood, PC; Longley, M; Greene, G; Morgan, G; Watkins, J; Pickering, J; Watkins, A; Protty, M; Bayer, A; Gallacher, J (Journal of Lifestyle Medicine, 2020)
Behaviors which are associated with the preservation of health include nonsmoking, regular exercise, a low body weight, a healthy diet, and a low alcohol intake. Together, as a healthy lifestyle, these have been shown to be associated with marked protection against a wide range of diseases: diabetes, vascular disease, cancer, and dementia. On the other hand, the protection associated with statins and aspirin, the two most commonly used preventive drugs, is limited to vascular disease and, probably for aspirin, cancer.